Fatigue behavior of pultruded fiberglass tubes under tension, compression and torsion (Fracture and Structural Integrity, 2024)
This work is devoted to an experimental investigation of fatigue behavior of pultruded fiberglass tubes under uniaxial tension, compression and torsion. Static tests were carried out; a presence of postcritical deformation stage during torsion is noted. Regularities of inhomogeneous strain fields evolution are analyzed using digital image correlation method. Fatigue curves are built for four cyclic loading modes: tension-tension, compression-compression, tension-compression and torsion. An analysis of specimens' fractures is carried out, typical damaging mechanisms are revealed. Residual dynamic stiffness data is obtained and studied using a previously proposed fitting model. Results demonstrate model's high descriptive capability and its flexibility to describe two-staged and three-staged stiffness degradation curves. An influence of loading mode on a shape of these curves is found out. Model parameters' dependence on maximum stress value during the loading cycle is studied using the Pearson's correlation coefficient. The necessity of multiaxial fatigue behavior investigation of pultruded fiberglass tubes is concluded.
Keywords: Polymer composite; Pultruded fiberglass tubes; Fatigue; Damage accumulation; Stiffness degradation; Digital image correlation